2013
DOI: 10.1159/000354253
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Crosstalk between the Estrogen Receptor and Human Epidermal Growth Factor Receptor 2 Signaling Pathways in Breast Cancer: Molecular Basis and Clinical Implications

Abstract: The estrogen receptor (ER) and/or the human epidermal growth factor receptor 2 (HER2) signaling pathways are the dominant drivers of cell proliferation and survival in the majority of human breast cancers. As a result, targeting these pathways provides the most effective therapies in appropriately selected patients. Nevertheless, resistance to both endocrine and anti-HER2 therapies occurs frequently and represents a major clinical challenge. Compelling preclinical and clinical evidence relates this treatment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
98
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 48 publications
4
98
0
2
Order By: Relevance
“…Basic research studies have reported that heterogeneous tumors, such as ER‐positive/HER2‐positive tumors, are more resistant to chemotherapeutic agents . The mechanism of crosstalk between ER and HER2 may be associated with resistance to chemotherapy and changes in HER2 status . Another possible factor might be a different pCR rate after NAC according to ER status.…”
Section: Discussionmentioning
confidence: 99%
“…Basic research studies have reported that heterogeneous tumors, such as ER‐positive/HER2‐positive tumors, are more resistant to chemotherapeutic agents . The mechanism of crosstalk between ER and HER2 may be associated with resistance to chemotherapy and changes in HER2 status . Another possible factor might be a different pCR rate after NAC according to ER status.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these overlapping genes have an AP-1 motif in their promoter/enhancer regions. Interestingly, the upregulated overlapping genes belong to a network of GFRs, stress-related kinases, and signaling molecules activated by the microenvironment, all of which have been implicated in endocrine resistance [26]. These data suggest that AP-1, by engaging altered ER-dependent genomic networks, may act as a major node integrating diverse signaling pathways mediating endocrine resistance.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence to suggest that interactions between HER2 and hormone-receptor pathways play an important role in disease progression and that there is extensive, complex, bidirectional, crosstalk between the HER2 and ER pathways [44]. Immune signatures have been reported to have a predictive or prognostic role mostly in ER-negative breast cancers [4548].…”
Section: Discussionmentioning
confidence: 99%